The genus Manota Williston (Diptera: Mycetophilidae) in Thailand, with the description of seven new species - Hippa, Heikki; Papp, László (Zootaxa, 2007)
Seven new species of Manota Williston are described from Thailand: M. bifida, M. dentata, M. forceps, M. inusitata, M. mirifica, M. occulta, and M. secreta. Nine Manota species, which were recently described from West Malaysia, are here recorded as new for the fauna of Thailand: M. heptacantha Hippa, M. oligochaeta Hippa, M. ovata Hippa, M. pectinata Hippa, M. perpusilla Hippa, M. plusiochaeta Hippa, M. procera Hippa, M. roslii Hippa, and M. ulu Hippa. M. biunculata Hippa, which was recently described from New Guinea, is also recorded from Thailand. The number of the Oriental species of Manota now stands at 37.